Effectiveness of osteoporosis prevention instruction program on nursing college students’ knowledge at Baghdad University - Abdul-Hameed, Huda; mohammed, Fatin (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): Assess the effectiveness of osteoporosis prevention instruction program on nursing college students’ knowledge at Baghdad University. Methodology: A quasi-experimental design was used to assess the effectiveness of osteoporosis prevention instruction program on nursing college students at University of Baghdad from April 2011 to September 2011. A random sample consisted of (40) females students from first year of Nursing College Baghdad University. The data was collected by using constructed questionnaire, which consists of three parts. Part one: consists of demographic information and health characteristics .Part two: consists of students’ daily life behaviors which include, dietary behaviors, and sport behaviors. Part three: consists of questions regarding students’ knowledge about osteoporosis, it contains three domains which are: Domain I: Anatomy and physiology of bones. Domain II: Nutritional elements those are necessary for bones building. Domain III: Osteoporosis. Reliability of the questionnaire is determined through the pilot study and the validity through a panel of (14) experts. Descriptive statistical analysis procedures and inferential statistical analysis procedures were employed for data analysisand all the statistical procedures were tested at P value ≤0.05. Results: The results revealed that 6 of 9 dietary behaviors of the students was good and the knowledge of the students concerning osteoporosis was low before implementation of the program but after implementation of the instruction program the knowledge of the students are highly improved. The effectiveness of the program is not affected by demographic characteristics and daily life behaviors, that means the program can be implemented for all females students and achieve the objectives of the program. Recommendations: The study recommended that science curriculums at all educational levels (pre-school, elementary, high school, college, and nursing schools) should be developed to address risk factors and preventive behavioral health lifestyle related to osteoporosis. Future researches on osteoporosis prevention should focus on a younger population, namely adolescents, to improve their knowledge of osteoporosis early enough to influence their self-efficacy for their health lifestyle behavioral changes.